LEARNING THE LANGUAGE OF DIGITAL RESIDENTS (DRS): A NATURALIZATION FORMULA FOR DIGITAL VISITORS (DVS) - Cheta Williams; Gladys Charles-Ogan (European Scientific Journal, ESJ, 2015)
The empirically survey design study was aimed at ascertaining how four hundred (400) Digital Visitors (DVs) in four (4) higher institutions in Nigeria now speak the language of the Digital Residents (DRs). A major finding was that it was not necessarily the educational training they had but such other measures as; ownership of personal computer (PC) and other information and communications technology (ICT) tools, personal development or periodic training, hands-on experience approach, passion for ICT tools/devices demonstration approach by experts and regular access to ICT tools/devices. The recommendations made were tied direct and drawn from these measures. The training of educators should not be a more advocacy of ICT integration but should emphasize application if the educators must be abreast of simple operational lint of ICT tools.